A prospective clinical evaluation of the diagnostic accuracy of the SARS-CoV-2 rapid antigen test using anterior nasal samples. Issue 6 (June 2022) - Akashi, Yusaku; Horie, Michiko; Takeuchi, Yuto; Togashi, Kenichi; Adachi, Yuki; Ueda, Atsuo; Notake, Shigeyuki; Nakamura, Koji; Terada, Norihiko; Kurihara, Yoko; Kiyasu, Yoshihiko; Suzuki, Hiromichi
Abstract: Introduction: The diagnostic accuracy of antigen testing of anterior nasal (AN) samples for the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has not been evaluated in the Japanese population. This study assessed the diagnostic accuracy of the Roche SARS-CoV-2 rapid antigen test (rapid antigen test) using AN samples. Methods: Two AN samples and one nasopharyngeal (NP) sample were collected from individuals undergoing screening for SARS-CoV-2 infection. The results of the rapid antigen test and the reverse-transcription polymerase chain reaction (RT-PCR) test using AN samples were compared to those of RT-PCR tests using NP samples. Results: Samples were collected from 800 participants, 95 and 110 of whom tested positive for SARS-CoV-2 on RT-PCR tests of AN and NP samples, respectively. The overall sensitivity/specificity of the AN rapid antigen test and AN RT-PCR were 72.7%/100% and 86.4%/100%, respectively. In symptomatic cases, the sensitivities of the AN rapid antigen test and AN RT-PCR were 84.7% and 94.9%, respectively. In asymptomatic cases, the sensitivities of the AN rapid antigen test and AN RT-PCR were 58.8% and 76.5%, respectively. The sensitivity of the AN rapid antigen test was over 80% in cases with cycle threshold (Ct) values < 25; it significantly decreased with an increase in the Ct values (p < 0.001). Conclusion: The rapid antigen test with AN samples had a favorable sensitivity, especially in symptomatic cases or in cases with Ct values < 25. It gave no false-positive results. Compared with AN-RT PCR, the AN rapid antigen test had a modestly lower sensitivity in asymptomatic cases.